Collagen VI regulates peripheral nerve myelination and function. Issue 3 (25th November 2013) - Chen, Peiwen; Cescon, Matilde; Megighian, Aram; Ronaldo, Paolo
Abstract : Collagen VI is an extracellular matrix protein with broad distribution in several tissues. Although Col6a1 is expressed by Schwann cells, the role of collagen VI in the peripheral nervous system (PNS) is yet unknown. Here we show that Schwann cells, but not axons, contribute to collagen VI deposition in peripheral nerves. By using Col6a1‐null mice, in which collagen VI deposition is compromised, we demonstrate that lack of collagen VI leads to increased myelin thickness ( P <0.001) along with 60–130% upregulation in myelin‐associated proteins and disorganized C fibers in the PNS. The hypermyelination of PNS in Col6a1 –/– mice is supported by alterations of signaling pathways involved in myelination, including increase of P‐FAK, P‐AKT, P‐ERK1, P‐ERK2, and P‐p38 (4.15, 1.67, 2.47, 3.34, and 2.60‐fold, respectively) and reduction of vimentin (0.49‐fold), P‐JNK (0.74‐fold), and P‐c‐Jun (0.50‐fold). Pathologically, Col6a1 –/– mice display an impairment of nerve conduction velocity and motor coordination ( P <0.05), as well as a delayed response to acute pain stimuli ( P <0.001), indicating that lack of collagen VI causes functional defects of peripheral nerves. Altogether, these results indicate that collagen VI is a critical component of PNS contributing to the structural integrity and proper function of peripheral nerves.—Chen, P., Cescon, M., Megighian, A., Bonaldo, P. Collagen VI regulates peripheral nerve myelination and function. FASEB J. 28, 1145–1156 (2014). www.fasebj.org